Monotheistic Characteristics of Hinduism from the Perspective of Selected Muslim Scholars: A Comparative Review - Ibrahim, Asad; Mohd Khambali @ Hambali, Khadijah; Ghazali, Alwani; Zainal Abidin, Azmil (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
Numerous studies by Muslim scholars have explored the monotheistic nature of Hinduism, with contrasting findings. Several scholars, such as al-Mas‘udi, al-Maqdisi, and al-Biruni, assert that Hinduism embraces the unity of God. Conversely, another group of scholars, including Abu Zahra and Ahmad Jasim, contends that Hinduism is fundamentally polytheistic. Additionally, some authors argue that Hinduism partially, rather than entirely, advocates for monotheism. Some Muslim scholarly works also suggest that polytheism has been established in Hinduism more recently. Consequently, readers of these studies may find the monotheistic concept in Hinduism unclear. This article applies the traditional narrative method, describing and discussing prior literature from contextual and theoretical perspectives, to categorically explore and present Muslim scholarly works on the monotheistic characteristics of Hinduism. It also aims to address the extent and nature of disagreements among Muslim scholars on this concept. The significance of this study lies in understanding the views of Muslim researchers on the oneness of God in Hinduism, which will aid in developing policies that promote better coexistence within a multi-religious community.